A FAIR based approach to data sharing in Europe. (1st October 2022) - Strand, P; Coster, D P; Plociennik, M; de Witt, S; Klampanos, I A; Decker, J; Imbeaux, F; Artaud, J F; Bosak, B; Cummings, N; Fleury, L; Ikonomopoulos, A; et al.
Abstract: The European fusion research activities have, over recent decades, generated a vast and varied set of data. The volume and diversity of the data that need to be catalogued and annotated make the task of organising and making the data available within a broader environment very challenging. Nevertheless, there are strong scientific drivers as well as incentives and mandates from national research agencies suggesting that a more coherent approach to data referencing, dissemination and sharing would provide strong benefits to the fusion research community and beyond. Here, we discuss the technical requirements and developments needed to transition the current, and future, range of fusion research data to an open and Findable, Accessible, Interoperable, and Reusable data sharing structure guided by the principle 'as open as possible, as closed as necessary'. Here we propose a set of recommendations and technical implementations needed to form a European data sharing environment for the fusion research programmes. Consistency with the emerging IMAS (ITER Integrated Modelling and Analysis Suite) infrastructure is considered to facilitate future deployments.